PENANGANAN KESALAHAN TAMPILAN MONITOR REMOTE CONTROL SYSTEM UNIT (RSCU) PADA MODUL DVOR – (STUDI KASUS BANDARA INTERNASIONAL RAJA HAJI FISABILILLAH TANJUNGPINANG) - Indah Vusvita Sari (Jurnal Penelitian)
DVOR is one of the air navigation equipment used to monitor air transportation travel in the field of aviation. DVOR plays an important role in aviation safety and security, especially in guiding the aircraft so that it can land perfectly at the destination airport. If there is an alarm on the RCSU DVOR, it is very dangerous for flight safety. The presence of an alarm on the DVOR RCSU indicates a problem with the DVOR equipment itself, so it is necessary to analyze the handling or repair of the DVOR equipment so that it can operate normally again in order to create a good navigation system to ensure flight safety and security. In this case, the cause of the alarm that occurred at the RCSU located in the Perum LPPNPI Tanjungpinang branch was the burning of the MOSFET component in the TX1 module. Handling is done by checking physically.